Correlation of Expression p16 on Genital Wart Lesions with Various Degrees of Cervical Dysplasia - Asri Rahmawati; Damayanti Damayanti; Cita Rosita SP; Hans Lumintang (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2014)
Introduction: Infection of Human Papillomavirus (HPV) can cause condylomata acuminata. High-risk HPV types have proteins E6 and E7 called “oncoprotein” for its role in the occurrence of cancer. E7 protein causing no active bond pRb and E2F is regulated by CDK inhibitors, such as p16INK4a . Overexpression p16INK4a could be obtained from pre cancerous lesions. Pap smear, the standard screening method, is performed to detect early malignancy of the cervix, but have low sensitivity. The presence of tumor markers, p16INK4 ,will help early detection of malignancy. Purpose: To evaluate the profile of p16INK4a expression in condylomata acuminata lesions with various degrees of cervical dysplasia. Methods: Discriptive, observational, cross seetional study by performed p16INK4a immunohistochemical examination in lesions condylomata acuminata and cytologic examination on cervical biopsy. Results: Results of cervical cytology (pap smear) from 18 samples showed Low-grade Squamous Intraepithelial Lesions (LSIL) in 10 patients (55.6%) and Negative for Intraepithelial Lesion or Malignancy (NILM) in 8 patients (44.4%). Immunohistochemical examination obtained p16INK4a expression with score of 1 (sporadic) in 8 patients (44.4%), with score of 2 (focal) in 7 patients (38.9%) and with score of 3 (diffuse) in 3 patients (16.7%).  From 3 patients with diffuse expression of p16INK4a , 2 patients (66,6%) showed LSIL from cytology cervix and 1 patient (33,3%) revealed NILM. Spearman correlation test results showed no significant correlation between p16INK4a expression in cervical dysplasia with p = 0.24 (p> 0,05). Conclusion: There were three samples of diffuse, with most of Low-grade Squamous Intraepithelial Lesions (LSIL) in cervical dysplasia, it indicates there is a potential of p16INK4a as a marker of malignancy in condylomata acuminata. Key words : condylomata acuminata, p16INK4a , cervical dysplasia.